Representation of Black Feminism in Hidden Figures - Andre Ikhsano; Jakarudi Jakarudi (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2020)
Hidden Figures is a film based on the true story of three African American women who help NASA in the space race. The three African American women are Katherine G. Johnson, Mary Jackson, and Dorothy Vaughan. With the setting of the 1960s era, these three women are fighting against a climate of segregation (separation based on race or skin color) in their work environment (NASA). This study aims to explore Patricia Hill Collins’ theory of black feminism and to integrate it with Stella Ting-Toomey’s theory of face-negotiation. This research is based on a critical paradigm and uses a qualitative approach. Using Sara Mills’s critical discourse analysis as a data analysis technique, this study found a representation of black feminism in the film Hidden Figures. The discrimination experienced by the characters is in the form of racism, sexism, and classism. However, the resistance carried out by the characters is through self definition, not in safe spaces as mentioned by Collins. The characters also do not avoid conflict, but use a negotiation approach with a compromising style to achieve a win-win solution.Keywords: Black feminism, face-negotiation, racism, sexism, classism ABSTRAKHidden Figures adalah film yang diangkat berdasarkan kisah nyata tiga perempuan Afro-Amerika yang membantu NASA dalam space race. Ketiga perempuan Afro-Amerika itu adalah Katherine G. Johnson, Mary Jackson, dan Dorothy Vaughan. Dengan setting waktu era 1960-an, ketiga perempuan ini berjuang melawan iklim segregasi (pemisahan berdasarkan pada ras atau warna kulit) di lingkungan kerja mereka (NASA). Penelitian ini bertujuan untuk mendalami teori black feminism Patricia Hill Collins dan hendak mengintegrasikannya dengan teori face-negotiation Stella Ting-Toomey. Penelitian ini didasarkan pada paradigma kritis dan menggunakan penekatan kualitatif. Menggunakan analisis wacana kritis Sara Mills sebagai teknik analisis data, penelitian ini menemukan representasi black feminism di dalam film Hidden Figures. Diskriminasi yang dialami para tokoh adalah berupa racism, sexism, dan classism. Akan tetapi, perlawanan yang dilakukan para tokoh adalah melalui self definition, tidak dilakukan dalam safe spaces sebagaimana disinggung oleh Collins. Para tokoh juga tidak menghindari konflik, namun menggunakan pendekatan negosiasi dengan gaya compromising style dalam mencapai win-win solution.Kata Kunci: Black feminism, face-negotiation, racism, sexism, classism